LncRNA EN-90756 promotes CPB2-induced proliferation and inhibits apoptosis in IPEC-J2 cells by affecting the JAK-STAT signaling pathway activation - Yang, Jiaojiao; Zhang, Juanli; Yang, Qiaoli; Huang, Xiaoyu; Yan, Zunqiang; Wang, Pengfei; Gao, Xiaoli; Li, Jie; Li, Na; Gao, Yi; Gun, Shuangbao (Frontiers in Microbiology, 2023)
Background Long non-coding RNAs (lncRNAs), as key regulators, are closely associated with the development of a variety of disease. However, the mechanisms by which lncRNAs regulate Clostridium perfringens type C induced piglet diarrhea are unclear. Methods In the present study, we explored the expression and characterization of lncRNAs in a C. perfringens beta2 (CPB2) toxin-treated intestinal porcine epithelial cell line-J2 (IPEC-J2) using RNA-sequencing (RNA-seq). Results A total of 6,558 lncRNAs were identified, of which 49 lncRNAs were significantly differentially expressed between the control and CPB2 groups. Functional enrichment analysis showed that the target genes of differentially expressed lncRNA EN-90756 were mainly associated with defense response to virus, and negative regulation of apoptotic process. LncRNA EN-90756 was significantly up-regulated in IPEC-J2 cells at different time points after CPB2 treatment. Functionally, knockdown of lncRNA EN-90756 might regulate the proliferation and apoptosis of IPEC-J2 cells by affecting the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway. LncRNA EN-90756 may be involved in CPB2 toxin-induced piglet diarrhea by regulating the expression of its target gene MX1 (encoding MX dynamin like GTPase 1). Conclusion Long non-coding RNA EN-90756 affected the antiviral ability of IPEC-J2 cells by regulating the expression of MX1. Meanwhile, lncRNA EN-90756 might regulate cell proliferation and apoptosis by affecting JAK-STAT signaling pathway activation. These findings provide novel perspectives and directions for further exploration of the regulatory mechanisms of lncRNAs on CPB2 toxin-induced diarrhea in piglets.